Gestión administrativa financiera y su incidencia en el otorgamiento de créditos de la cooperativa de ahorro y crédito de porvenir período 2014-2015, manual de procedimiento. - Ramos Zambrano, Clemencia Raquel (2015)
Cooperative "El Porvenir" is an internal institution of Wong group, which is dedicated to the supply of financial products and services to company employees Reybanpac, so it is necessary to develop an assessment of the impact of administrative management - financial in granting credit cooperative El Porvenir. To facilitate opportunities for partners to improve good living from their families by promoting a culture of savings and facilitate timely credit. Existing conditions of the economy, make financial institutions contribute to the development of enterprises, for this reason the credit union El Porvenir is useful for economic development Quevedo Canton, administrative financial management principles that have consider institutions to achieve objectives and goals, achieving the operational performance of the local market. In this respect the Cooperative in the diagnosis made a weak credit system and poor management planning was observed, so this investigation is fully justified to determine the administrative management and its impact on profitability. Therefore the objective of the research is aimed at evaluating the effect of administrative management with regard to the profitability of the cooperative El Porvenir, in the same way the hypothesis is inadequate administrative financial adversely affects the system of granting credit in the Credit Union Credit El Porvenir. To raise the manual of procedures for the award of credits attached to the reality of the institution, and in this way the cooperative develop its operations properly.